2008
DOI: 10.1111/j.1365-2893.2008.01027.x
|View full text |Cite
|
Sign up to set email alerts
|

Modern epidemiology of hepatitis A in the north‐western region of the Russian Federation

Abstract: The epidemiological features of hepatitis A virus (HAV) infection were studied in eleven territories located in the north-western region of the Russian Federation. The dynamics of HAV infection in Russia and in the region were evaluated during a 17-year period. The age-specific incidence was calculated and 229 305 patients with acute HAV were identified. The analysed database included HA mixed with other viral hepatitis infections: it included information about 8 809 HAV patients. Special attention has been pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2008
2008
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 11 publications
0
5
0
1
Order By: Relevance
“…Increased access to safe water and adequate sanitation, usually in urban but not rural areas, has decreased HAV infections among children resulting in growing populations of susceptible persons. As a consequence of this epidemiological shift, countries have reported an increased incidence of symptomatic and fulminant HepA with significant morbidity and mortality among susceptible children from urban populations [1–6]. In some developing countries circulation of HepA virus is enhanced due to the co‐existence of populations with low and high socio‐economic conditions.…”
Section: Hepatitis a Virus Infectionmentioning
confidence: 99%
“…Increased access to safe water and adequate sanitation, usually in urban but not rural areas, has decreased HAV infections among children resulting in growing populations of susceptible persons. As a consequence of this epidemiological shift, countries have reported an increased incidence of symptomatic and fulminant HepA with significant morbidity and mortality among susceptible children from urban populations [1–6]. In some developing countries circulation of HepA virus is enhanced due to the co‐existence of populations with low and high socio‐economic conditions.…”
Section: Hepatitis a Virus Infectionmentioning
confidence: 99%
“…In St. Petersburg region of neighboring Russia, the seropositivity numbers were much higher, at about 20% for 10-year olds and 70% for 40-year olds in 1998 [Mukomolov et al, 2001]. In 2006 the seropositivity numbers were still high, at 28.3% for those aged 20-29, 39.6% for those aged 30-39, and 71.9% for those aged 40þ [Shliakhtenko et al, 2008]. A previous review has shown that the figures by region in the rest of Europe are higher than in Finland [Jacobsen and Koopman, 2004].…”
Section: Introductionmentioning
confidence: 96%
“…In Russia, the most significant changes in recent years in the epidemiology of hepatitis A were observed in north‐west Russia and in St Petersburg, the central city of this region. The highest incidence rate was registered in St Petersburg in 2004 (93.4 per 100,000), decreasing thereafter to 17.5 per 100,000 in 2007 [Shliakhtenko et al, 2008] and even to 7.7 per 100,000 in 2009. The latest HAV seroepidemiological study in the city was conducted in 2009 [Mukomolov et al, 2010] and revealed a dramatic reduction in immunity to HAV in the population of the city.…”
Section: Introductionmentioning
confidence: 99%